2020
DOI: 10.1111/infa.12325
|View full text |Cite
|
Sign up to set email alerts
|

Infant screen exposure links to toddlers' inhibition, but not other EF constructs: A propensity score study

Abstract: Technology is pervasive in homes of families with young children, despite evidence for negative associations between infant exposure to screen‐based media and cognitive development that has led the American Academy of Pediatrics (AAP) to discourage parents from exposing children under the age of 18 months to any kind of screen time (AAP, 2016). Here, we apply a propensity score matching approach to estimate relations between electronic screen‐based media use in infancy and executive function in early toddlerho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 44 publications
1
35
1
1
Order By: Relevance
“…The longitudinal findings of the current study are concordant with prior longitudinal findings (e.g., Barr et al, 2010;McHarg et al, 2020). This association may be due to increased screen use replacing activities that are important for cognitive development, such as playing with manipulatives and engaging in imaginative play.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The longitudinal findings of the current study are concordant with prior longitudinal findings (e.g., Barr et al, 2010;McHarg et al, 2020). This association may be due to increased screen use replacing activities that are important for cognitive development, such as playing with manipulatives and engaging in imaginative play.…”
Section: Discussionsupporting
confidence: 89%
“…First, the majority of extant research has used crosssectional data, making it impossible to disentangle directionality in the relations between media use and EF. Those few studies that have investigated longitudinal associations have found that screen time predicts worse EF-or at least components thereofat later time points (e.g., McHarg et al, 2020). However, it is also important to note that much of the work examining relations between media use and EF has been limited to either infants (e.g., McHarg et al, 2020) or preschool-aged children (e.g., Barr et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive body of work investigating the effects of manipulations of the A-not-B object retrieval task (considered a measure of response inhibition) is a prime example of this (Marcovitch & Zelazo, 1999). More recently, attention has increasingly focused on the study of individual differences in EFs as a means of delineating developmental mechanisms, and predicting influences on-and consequences of-early individual variation (Hendry et al, 2016;Hughes et al, 2020;McHarg et al, 2020;Pérez-Edgar et al, 2020). When embedded in longitudinal designs, such work has potential to illuminate the impact of environmental factors on EF development and to inform intervention design for populations showing, or at risk for, EF difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Although screen use has been linked to many aspects of early childhood development (e.g., language, health, sleep; for reviews, see Duch et al, 2013 ; Hale & Guan, 2015 ), research in recent years has highlighted potential associations with young children’s emerging executive function skills; in particular, the ability to exert inhibitory control ( Barr et al, 2010 ; McHarg et al, 2020a ). Executive functions (EFs) refer to core cognitive skills needed to control and guide behavior, commonly including inhibitory control, working memory, and cognitive flexibility ( Diamond, 2013 ; Lehto et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%